PENGARUH DISIPLIN KERJA DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PADA PT FIRST MEDIA TBK CABANG JAKARTA SELATAN - Jeni Andriani; Ninik Anggraini; Rr. Ayu Metarini (Sekolah Menengah Kejuruan (SMK) Pustek, 2023)
The purpose of this study was to determine the effect partially or simultaneously between Work Discipline and Job Satisfaction on Employee Performance at PT First Media Jakarta Selatan. The research method used is associative quantitative, using random sampling using the saturated sample method or using the entire population as a sample. This study uses calculations. Data analysis uses validity test, reliability test, classical assumption test, regression analysis, correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The result is that work discipline has a significant effect on employee performance with the regression equation Y = 2.184 + 0.939 X1 correlation coefficient of 0.776 meaning that the two variables have a very strong level of relationship. smaller than 0.05, it can be interpreted that Ha is accepted and Ho is rejected, so that it can be concluded that work discipline has a positive and significant effect on employee performance. Job satisfaction has a significant effect on work discipline with the regression equation Y = 6.210 + 0.856X2. correlation coefficient of 0.802 means that the two variables have a very strong level of relationship. The tcount value of the Organizational Culture variable is 5,323 greater than the ttable of 1.99962 with a significant level of 0 greater than 0.05, which means that Ha is accepted and Ho is rejected. So that it can be concluded partially that Job Satisfaction has a positive and significant effect on Employee Performance. Work Discipline and Job Satisfaction have a significant effect on Employee Performance with the regression equation Y = -2.085 + 0.505 X1 + 0.540X2. The value of the correlation coefficient or the level of influence between the independent variables and the dependent variable is 0.845, meaning that it has a very strong relationship. Fcount is 668.295 and a significance value is 0 while the Ftable value is at a significance level of 0.05 with df 1 (number of variables -1) 3-1 = 2, and df 2 (n-k-1) or = 63-2-1 = 0 obtained the F table value is 3.15. So it can be concluded that Fcount > Ftable (668.295 > 3.15) and significance <0.05 (0 <0.05), then Ha is accepted, so it can be concluded that work discipline and job satisfaction together affect performance Employee